Structural analysis of the cattle antibody repertoire - Clarke, JD (2022)
Cattle present an extreme immunological model, wherein immunoglobulin sequence diversification is achieved not through recombinational diversity, as in humans and mice, but by great heterogeneity in the length of the complementarity determining region #3 of the heavy chain (CDR3H), and by somatic hypermutation independent of antigenic contact. Bovine CDR3H lengths span 5 - 72 residues, with those containing >48 labelled as ‘ultralong’ and assumed to interact with epitopes typically invisible to paratopes with shorter CDR loops. Cattle also demonstrate preferential combination of V(D)J rearrangements without antigenic stimulus, inferring a structural relationship between bovine immunoglobulins that is not yet understood. This project aims to advance understanding of these relationships from a structural and functional context.